2019
DOI: 10.35188/unu-wider/2019/639-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foreign aid on income through international trade

Abstract: This article presents a review of recent studies that estimate the trade effects of foreign aid. It also provides new results obtained using panel data techniques to estimate the direct effects of aid on international trade accounting for countries' participation in free trade agreements, and the indirect effects that aid exerts on income through trade. A structural gravity model of trade augmented with aid and free trade agreement variables is estimated for a cross-section of 33 donor countries and 125 recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…From the perspective of development stages, studies have revealed that at the early stage of economic development, the recipient countries take benefits from aid but aid will weaken competitiveness of the recipient countries if they continue to receive aid without any efforts to absorb potential benefits of aid (Aitken & Harrison, 1999;A. G. Hu & Jefferson, 2002;Johansson & Pettersson, 2009;Martinez-Zarzoso, 2019). In the same way, if the NIS of the recipient country is vulnerable to socioeconomic and political problems, aid may not contribute positively and can act as obstacles in certain cases (Guillaumont & Chauvet, 2001;J.…”
Section: Development Aid and Innovationmentioning
confidence: 99%
“…From the perspective of development stages, studies have revealed that at the early stage of economic development, the recipient countries take benefits from aid but aid will weaken competitiveness of the recipient countries if they continue to receive aid without any efforts to absorb potential benefits of aid (Aitken & Harrison, 1999;A. G. Hu & Jefferson, 2002;Johansson & Pettersson, 2009;Martinez-Zarzoso, 2019). In the same way, if the NIS of the recipient country is vulnerable to socioeconomic and political problems, aid may not contribute positively and can act as obstacles in certain cases (Guillaumont & Chauvet, 2001;J.…”
Section: Development Aid and Innovationmentioning
confidence: 99%
“…Hansen and Tarp (1999) examined the effect of aid inflows on the growth rate of GDP per capita in developing countries. The findings showed that aid is positively associated with both growth and capital formation (see also Martínez-zarzoso, 2019; 348 IJOEM 15,2 Tang and Bundhoo, 2017;Karras, 2006;Mustafa et al, 2018;Yiew and Lau, 2018;Orji et al, 2019). In a related study on the SSA, Clemens et al (2004) contended that aid has a statistically significant impact on real per capita growth.…”
Section: Empirical Reviewmentioning
confidence: 98%